Synthesis of Poly(vinyl pyrrolidon-co-acrylamide) Flocculants by Radical Polymerization - Cakmak, Ismail; Tuter, Melek (Asian Journal of Chemistry, 2016)
The copolymerization of acrylamide (AAm) and 1-vinyl-2-pyrrolidon (VP) using disodium salt of 4,4'-azo-bis(4-cyanopentanoic acid) (ACPA-Na) as water-soluble catalyst was carried out to yield poly(acrylamide-co-1-vinyl-2-pyrrolidon) in aqueous solution at 70°C. The cross-linking of the polymer formation of water-insoluble polymer could be avoided by the addition of K2CO3 to raise the pH of the reaction mixture above 7.0. The copolymers were used as flocculants in the flocculation of suspension of tincal concentrate and showed good flocculating properties.